Предмет: Алгебра, автор: bakunina99

Упростите выражения 

1. frac{4}{a} - frac{2a^{2} - 9b^{2} }{ab} + frac{2a}{b} 

 

2.frac{4a}{a^{2} - 4b^{2} } - frac{4}{a + 2b} 

Ответы

Автор ответа: arsenlevadniy
0

frac{4}{a}-frac{2a^2-9b^2}{ab}+frac{2a}{b}=frac{4cdot b-(2a^2-9b^2)+2acdot a}{ab}=frac{4b-2a^2+9b^2+2a^2}{ab}= \ =frac{4b+9b^2}{ab}=frac{b(4+9b)}{ab}=frac{4+9b}{a}

 

 frac{4a}{a^2-4b^2}-frac{4}{a+2b}=frac{4a}{(a-2b)(a+2b)}-frac{4}{a+2b}=frac{4a-4(a-2b)}{(a-2b)(a+2b)}= \ =frac{4a-4a+8b}{(a-2b)(a+2b)}=frac{8b}{a^2-4b^2}

Похожие вопросы
Предмет: Алгебра, автор: КрокодилГена555
Предмет: Математика, автор: hahahaha30